2015
DOI: 10.1016/j.apjtm.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of telmisartan on rats with renal failure and its mechanism

Abstract: A B S T R A C TObjective: To study the protective effect of telmisartan on rats with renal failure and its mechanism. Methods: 60 Wistar rats were chosen as study objective, and were divided into 4 groups randomly: 15 in group A (sham operation group), 15 in group B (model group), 15 in group C (telmisartan group) and 15 in group D (telmisartan + GW9962 group). The difference of survival rate, blood-urine biochemical indexes, renal pathological change, and the expression level of PPARg and nNOS were compared. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Furthermore, telmisartan is able to attenuate renal podocyte apoptosis and autophagy-associated protein expression levels (7). Finally, telmisartan may have anti-fibrotic effects in human mesangial cells and reportedly decreased the expression levels of PPARγ and nNOS to delay the progression of renal failure (8)(9)(10)(11). Long term follow-up of the present case included the thorough and persistent monitoring for disease progression, which may be recommended for telmisartan as a first-line treatment for CG.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Furthermore, telmisartan is able to attenuate renal podocyte apoptosis and autophagy-associated protein expression levels (7). Finally, telmisartan may have anti-fibrotic effects in human mesangial cells and reportedly decreased the expression levels of PPARγ and nNOS to delay the progression of renal failure (8)(9)(10)(11). Long term follow-up of the present case included the thorough and persistent monitoring for disease progression, which may be recommended for telmisartan as a first-line treatment for CG.…”
Section: Discussionmentioning
confidence: 82%
“…Medicinal approaches include inhibitors of angiotensin-converting enzyme (ACE) and of angiotensin II receptor blockers (ARB) (25). There are certain common adverse effects of ACE inhibitors, including coughing, renal dysfunction and hyperkalemia, and, in particular, prominent angioedema (11). ARB drugs are effective in reducing the risk of end-stage renal disease in patients with diabetic nephritis and decreased serum creatinine levels two-fold compared to those obtained with ACE inhibitors (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Renal failure is complete or partial damage of kidney functions that may be chronic and acute. 8 The life of patients with renal failure depends on dialysis or kidney transplant which are costly. Li et al, 9 reported that ethanolextract of Chinese chive water in a concentration of 200 mg/kg/day given to adenine-induced chronic renal failure (CRF) mice model led to significant decrease of renal pathological damage to 48.1%, and decrease values of serum creatinine and blood urea nitrogen to 87.7% and 83.9%, respectively.…”
Section: Introductionmentioning
confidence: 99%